Bronchial artery chemoembolization in the treatment of refractory central lung cancer with atelectasis - Liu, Yujin; Zhang, Xiumei; Zhang, Fenxiang; Song, Weixiang (Frontiers in Oncology, 2024)
Objective: This study aims to explore the clinical application of bronchial artery chemoembolization (BACE) in managing refractory central lung cancer with atelectasis. Methods: The retrospective case series includes patients diagnosed with refractory central lung cancer and atelectasis who underwent BACE treatment at Yueyang Integrated Traditional Chinese and Western Medicine Hospital, affiliated with Shanghai University of Traditional Chinese Medicine, from January 2012 to December 2021. Results: All 30 patients with lung cancer successfully underwent BACE procedures. Their ages ranged from 62 to 88 years, with an average age of 67.53. The treatment interval was 21 days, and the treatment cycle ranged from 2 to 12 times, averaging 4.13 times. During the BACE procedures, the Karnofsky Performance Status (KPS) score after 2 to 3 BACE cycles showed a significant improvement (82.0 ± 10.1 vs 68.3 ± 14.0, P < 0.001) than that of before BACE. Only nutritional support and symptomatic treatment were performed after BACE, and no major hemoptysis were observed. During follow-up, 23 cases resulted in mortality, while seven survived. The median progression-free survival (PFS) and overall survival (OS) were 7.0 (95% CI: 4.6-9.4) and 10.0 (95% CI: 6.2-13.8) months, respectively, with 1-, 2-, and 3-year survival rates of 84.0%, 53.5%, and 11.3%, respectively. Eight cases exhibited bronchial recanalization and relief of atelectasis. According to the RECIST scale, there were 4 cases of complete response (CR), 16 cases of partial response (PR), 9 cases of stable disease (SD), and 1 case of progressive disease (PD). No serious adverse events were reported. Conclusion: BACE might be a safe intervention for refractory central lung cancer accompanied by atelectasis. The procedure exhibits satisfactory outcomes in tumor control, atelectasis relief, and enhancement of quality of life, warranting further investigation.